'Crowded Places Are Everywhere We Go': Crowds, Emergency, Politics. (March 2015) - Aradau, Claudia
'Crowded places' have recently been problematized as objects of terrorist attacks. Following this redefinition of terrorism, crowds have been reactivated at the heart of a security continuum of counter-terrorism, emergency planning and policing. How does the crowd referent recalibrate security governance, and with what political effects? This article argues that several subtle reconfigurations take place. First, counter-terrorism governance derives the knowledge of crowds from 'generic events' as unexpected, unpredictable and potentially catastrophic. This move activates 19th-century knowledge about crowds as pathological, while the spatial referent of 'crowded places' reconfigures workplaces as crowded places and workers as crowds. Second, new guidance for emergency planning and policing deploys a more rational approach to crowds, put forward in recent psychosocial approaches. These modes of knowledge derive 'generic crowds' from normal social relations rather than extraordinary events. Generic events and generic crowds effectively depoliticize crowds, as they exclude a more radical generic politics, in which crowds are not derivable, but negate determination.